Assessing the effects of the first 2 years of industry‐led badger culling in England on the incidence of bovine tuberculosis in cattle in 2013–2015. Issue 18 (4th August 2017) - Brunton, Lucy A.; Donnelly, Christl A.; O'Connor, Heather; Prosser, Alison; Ashfield, Stuart; Ashton, Adam; Upton, Paul; Mitchell, Andrew; Goodchild, Anthony V.; Parry, Jessica E.; Downs, Sara H.
Abstract: Culling badgers to control the transmission of bovine tuberculosis (TB) between this wildlife reservoir and cattle has been widely debated. Industry‐led culling began in Somerset and Gloucestershire between August and November 2013 to reduce local badger populations. Industry‐led culling is not designed to be a randomized and controlled trial of the impact of culling on cattle incidence. Nevertheless, it is important to monitor the effects of the culling and, taking the study limitations into account, perform a cautious evaluation of the impacts. A standardized method for selecting areas matched to culling areas in factors found to affect cattle TB risk has been developed to evaluate the impact of badger culling on cattle TB incidence. The association between cattle TB incidence and badger culling in the first 2 years has been assessed. Descriptive analyses without controlling for confounding showed no association between culling and TB incidence for Somerset, or for either of the buffer areas for the first 2 years since culling began. A weak association was observed in Gloucestershire for Year 1 only. Multivariable analysis adjusting for confounding factors showed that reductions in TB incidence were associated with culling in the first 2 years in both the Somerset and Gloucestershire intervention areas when compared to areas with no culling (incidence rate ratio (IRR): 0.79, 95% CI: 0.72–0.87, p < .001 and IRR: 0.42, 95% CI: 0.34–0.51, p < .001, respectively). An increase in incidence was associated with culling in the 2‐km buffer surrounding the Somerset intervention area (IRR: 1.38, 95% CI: 1.09–1.75, p = .008), but not in Gloucestershire (IRR: 0.91, 95% CI: 0.77–1.07, p = .243). As only 2 intervention areas with 2 years of data are available for analysis, and the biological cause–effect relationship behind the statistical associations is difficult to determine, it would be unwise to use these findings to develop generalizable inferences about the effectiveness of the policy at present. Abstract : We describe the effects of industry‐led badger culling in England on bTB incidents in cattle herds in the first two years of the intervention. Descriptive analyses without controlling for confounding showed no association between the intervention and TB incidence for Somerset, or for either of the buffer areas for the first or second year since culling began. Multivariable analysis adjusting for confounding factors showed that reductions in cattle TB incidence were associated with the industry‐led badger culling in the first two years in both the Somerset and Gloucestershire intervention areas, and an increase in incidence was associated with culling in the 2‐km buffer surrounding the Somerset intervention area, but not in Gloucestershire. As only two intervention areas with two years of follow‐up data are available for analysis here, it is unwise to develop generalizable inferences about the effectiveness of the policy at present.